2016
DOI: 10.1159/000447628
|View full text |Cite
|
Sign up to set email alerts
|

PPAR Agonists Promote the Differentiation of Porcine Bone Marrow Mesenchymal Stem Cells into the Adipogenic and Myogenic Lineages

Abstract: Purpose: The aim of this work was to evaluate the effect of PPAR agonists on the differentiation and metabolic features of porcine mesenchymal stem cells induced to the adipogenic or myogenic lineages. Methods: Bone marrow MSCs from neonate pigs were isolated and identified by cell proliferation, cell surface markers or the gene expression of stem cells (CD44, CD90, CD105 or Oct4 and Nanog, respectively). Cells were differentiated into adipose or muscle cells and treated with the PPAR agonists; adipogenic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 80 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Myogenic regulatory factors orchestrate the differentiation of MSCs into muscles cells. MyoD and Myogenin are believed to be early differentiation markers of myogenic differentiation, and Myf5 and MRF4 are believed to regulate terminal differentiation and cell fusion (Perez-Serrano et al, 2017). Similar to muscle development, MyoD and Myogenin are main muscle-specific transcription factors that are expressed during myogenic differentiation of MSCs (Gang et al, 2004, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Myogenic regulatory factors orchestrate the differentiation of MSCs into muscles cells. MyoD and Myogenin are believed to be early differentiation markers of myogenic differentiation, and Myf5 and MRF4 are believed to regulate terminal differentiation and cell fusion (Perez-Serrano et al, 2017). Similar to muscle development, MyoD and Myogenin are main muscle-specific transcription factors that are expressed during myogenic differentiation of MSCs (Gang et al, 2004, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Pérez‐Serrano et al (2017) observed that PBM‐MSCs from porcine neonate exhibited high proliferation and were positive for MSCs markers CD44, CD90, CD105 , and positive expression of stem cells genes ( OCT4, NANOG ). Subsequently, Nishimura et al (2019) reported that newborn PBM‐MSCs expressed positive MSCs markers CD29, CD44 , and CD90 and differentiated into chondrocytes, osteocytes, and adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Three 3.5 cm culture dishes (10 4 cells/dish, Corning Inc., Corning, NY, USA) were seeded with cells for each animal. Every 4 days, stationary subcultures were collected until the fourth passage, at which point adipogenic cultures were performed (Pérez‐Serrano et al, 2017). Daily observations of cells were made with an epifluorescence microscope (Olympus, Melville, New York, USA) equipped with a digital color camera and Motic Image Plus software 2.0 (Motic Asia, Hong Kong).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was indeed demonstrated that overexpression of activated β-catenin in MSC stimulated myogenic differentiation of these cells, and suppressed their adipogenic differentiation via downregulating the expressions of PPARγ and the CCAAT/enhancer binding protein C/EBPα [131]. More recently, it has also been demonstrated that PPAR agonists stimulate bone marrow mesenchymal stem cells to enter either the myogenic and adipogenic lineages [132]. Along the same line of experimentation, culture conditions have been established to obtain pure mesenchymal precursors from human embryonic stem cells, which can be differentiated into skeletal muscle cells, adipocytes, cartilage, and bone [133].…”
Section: Ppars In Muscle Wastingmentioning
confidence: 97%